The determinants of Malaysian trade balance: a Johansen and Juselius approach / Khairunnisa Azrin and Mohammad Amyrul Hafiz Azizan - Azrin, Khairunnisa; Azizan, Mohammad Amyrul Hafiz (Faculty of Business and Management, 2013)
This paper examines the short- and long-run relationships between trade balance,real exchange rates, income and money supply in the case of Malaysia. Data for the variables were obtained from World Development Indicators (WDI) from 1975 to 2010 The results based on the Johansen Juselius there is atleast two cointergration vector equation in the study using lag 1. Based on Johansen Juselius we found equilibrium relationship exists between trade balance and the determinants of trade. Based on Juselius there is two long run relationships appear in the model. It was from hypothesis none and atmost 1 where the figure of trace statistic is bigger than 5 % critical value. We also are using VECM test and Granger Causality test to examine the long run relationships and short run relationship in the model. We found that there is a directional relationship between GDP and REER because the probability is less than 0.05. There is also shows that there is only one short run relationship that appears in the model. Results shows that trade balance and real exchange effective rates have long run relationship because of negatives value result on VECM test. The result was supported by previous study by (2007) . A few policies implication can be recommended such as government should increase trade deficit of raw materials. Another than that, government also should increase export penetration to other country.Than there is two other recommendation on increasing food production to increase trade balance.